Confluence Bar of the São Pedro Brook in the Paraná River: Genesis and Environmental Importance - DOI 10.5216/bgg.v19i1.15302 - T.M, Turra; V.V, Marques; J.C, Stevaux (Boletim Goiano de Geografia, 2011)
.